Microstructural characterization and mechanical behavior of NiTi shape memory alloys ultrasonic joints using Cu interlayer - Zhang, Wei (2018)
This research was funded by National Key R&D Program of China under Grant 2018YFB1107900, the National Natural Science Foundation of China under Grant 51775091 and 51575383; Natural Science Foundation of Tianjin City under Grant 18JCQNJC04100; Science and Technology Project of Sichuan Province under Grant 2018GZ0284; Fundacao para a Ciencia e a Tecnologia (FCT-MCTES) under Grant PEst-OE/EME/UI0667/2014.